New Job Matches and Their Stability Before and During the Crisis - Amparo Nagore García; Arthur van Soest (Institute for the Study of Labor (IZA), 2015)
Using administrative records data from the Spanish Social Security Administration, we analyse the nature and stability of job matches starting in two different years: during the economic boom in 2005, and during the recession in 2009. We compare the individual and job and firm characteristics in the two samples and estimate Mixed Proportional Hazard Models distinguishing job-to-job, job-to-unemployment, and other transitions. We find that job-to-job transitions are pro-cyclical, while unemployment transitions are counter-cyclical. Individuals most affected by the economic crisis tend to be young males, living in regions with high unemployment rates, with low qualifications and working in manual occupations (particularly construction), and (especially Spanish speaking) immigrants. The positive relation between job stability and firm size is stronger during the recession.
Keywords: J64; C41; E32; 330; job tenure; business cycle; employment transitions; destination states; job-separation rate